The charge transport properties of dicyanomethylene-functionalised violanthrone derivatives - Sondos A. J. Almahmoud; Joseph Cameron; Dylan Wilkinson; Michele Cariello; Claire Wilson; Alan A. Wiles; Peter J. Skabara; Graeme Cooke (Beilstein Journal of Organic Chemistry)
The study of organic small molecule semiconductor materials as active components of organic electronic devices continues to attract considerable attention due to the range of advantages these molecules can offer. Here, we report the synthesis of three dicyanomethylene-functionalised violanthrone derivatives (3a, 3b and 3c) featuring different alkyl substituents. It is found that the introduction of the electron-deficient dicyanomethylene groups significantly improves the optical absorption compared to their previously reported precursors 2a–c. All compounds are p-type semiconductors with low HOMO–LUMO gaps (≈1.25 eV). The hole mobilities, measured from fabricated organic field-effect transistors, range from 3.6 × 10−6 to 1.0 × 10−2 cm2 V−1 s−1. We found that the compounds featuring linear alkyl chains (3b and 3c) displayed a higher mobility compared to the one with branched alkyl chains, 3a. This could be the result of the more highly disordered packing arrangement of this molecule in the solid state, induced by the branched side chains that hinder the formation of π–π stacking interactions. The influence of dicyanomethylene groups on the charge transport properties was most clearly observed in compound 3b which has a 60-fold improvement in mobility compared to 2b. This study demonstrates that the choice of the solubilising group has a profound effect on the hole mobility on these organic semiconductors.